Pengaruh Profitabilitas, Kepemilikan Manajerial, dan Gender Diversity Terhadap Penerapan Integrated Reporting - Alhafizh Afkar Akmal; Tri Utami Lestari (Owner : Riset dan Jurnal Akuntansi, 2023)
Integrated reporting is still a relatively new problem in the business world, there are not many studies or literature on this topic. Until now, the case study of a single organization has been the most common method of integrated reporting studies. financial and non-financial reports, corporate prospects, governance, and performance are provided through integrated reporting. Integrated reporting is expected to change the emphasis from short-term value created for shareholders to long-term value created for all stakeholders. The purpose of this study is to ascertain how the implementation of integrated reporting is affected by profitability, management ownership, and gender diversity. Real estate and property sector companies listed on the IDX from 2018 to 2021 are the study population. Purposive sampling is the method used with 21 listed companies. Panel data analysis is the analysis method used. According to the findings of this study, the probability value of the effect of profitability on integrated reporting is 0.0028 <0.05 so that profitability has a partial effect on integrated reporting. The probability value on the effect of managerial ownership on integrated reporting is 0.7792 > 0.05, therefore managerial ownership has no effect on integrated reporting partially. The probability value for the effect of gender diversity on integrated reporting is 0.8076 > 0.05, therefore gender diversity has no effect on integrated reporting partially in a sample of real estate and property sector companies listed on the IDX in 2018–2021